Students' Perception of The Genshin Impact Game in Their Vocabulary Mastery and 21st-Century Skills - Rizka Rahma Nuriyah; Aqila Thahira Sisfiamuhsha; Indira Marja Aulia; Fahriany (Universitas Cokroaminoto Palopo, 2024)
This paper presents students’ perception of the Genshin Impact game in their vocabulary mastery and 21st-century skills. The aim of the study was to describe how the Genshin Impact game contributes to 5th-semester students’ English vocabulary mastery in the English Education Major at the State Islamic University of Syarif Hidayatullah Jakarta and improves their 21st-century skills. Through a descriptive qualitative method, the study aimed to inform students that there are other alternatives to learning English vocabulary in a more interesting way, such as playing the Genshin Impact game. Based on the result of the data analysis, the researchers found that playing the Genshin Impact game contributes to students’ vocabulary mastery and allows them to apply the vocabulary they have learned from the game according to the context. Additionally, the participants’ 21st-century skills, such as critical thinking, creativity, and collaboration, increased after playing the Genshin Impact game. The researchers suggest that students can choose the Genshin Impact game as a medium to improve their vocabulary mastery and 21st-century skills.